2006
DOI: 10.1038/sj.emboj.7601187
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of PRC1 function at the initiation of X inactivation independent of PRC2 and silencing

Abstract: In mammals X inactivation is initiated by expression of Xist RNA and involves the recruitment of Polycomb repressive complex 1 (PRC1) and 2 (PRC2), which mediate chromosome-wide ubiquitination of histone H2A and methylation of histone H3, respectively. Here, we show that PRC1 recruitment by Xist RNA is independent of gene silencing. We find that Eed is required for the recruitment of the canonical PRC1 proteins Mph1 and Mph2 by Xist. However, functional Ring1b is recruited by Xist and mediates ubiquitination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

31
323
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 353 publications
(358 citation statements)
references
References 49 publications
31
323
0
1
Order By: Relevance
“…The role of H3 K27 trimethylation in PRC1 recruitment is widely assumed despite accumulating genetic data demonstrating PRC1 functions independent of PRC2 activity (3,15,16). Our experiments demonstrated that neither the chromodomains nor H3 K27 trimethylation were required for chromatin association by CBX proteins in cells, and chromatin-associated CBX proteins did not colocalize with H3 K27 trimethylation outside the inactive X.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The role of H3 K27 trimethylation in PRC1 recruitment is widely assumed despite accumulating genetic data demonstrating PRC1 functions independent of PRC2 activity (3,15,16). Our experiments demonstrated that neither the chromodomains nor H3 K27 trimethylation were required for chromatin association by CBX proteins in cells, and chromatin-associated CBX proteins did not colocalize with H3 K27 trimethylation outside the inactive X.…”
Section: Discussionmentioning
confidence: 68%
“…Despite the absence of detectable H3 K27 trimethylation in Suz12-deficient ES cells, similar levels of CBX8 and Bmi-1 binding to most genes is observed (3). Several PRC1 components are recruited to the inactive X in EED null cells, and CBX2 is recruited to heterochromatin in male pronuclei lacking EZH2 (15,16). Thus, in several cases PRC1 recruitment does not require PRC2 or H3 K27 trimethylation.…”
mentioning
confidence: 91%
“…Thus, a different PRC1 complex might be at play when RING1 is recruited by Xist to the X inactivation center. 31 One should keep in mind, however, that mechanisms other than H2A ubiquitylation could also contribute to PRC1 function. This has been clearly demonstrated for the case of L3MBTL2, which does not seem to stimulate RING1A/RING1B activity in vitro, and was therefore suggested to act as a recruiter exclusively.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding these mechanisms requires the identification of new Ring1B/Rnf2 partners and the characterization of the complexes they form. These new complexes would also explain additional chromatin-targeting mechanisms unveiled in studies on the inactivation of mammalian X chromosome (silenced as a gene dosage compensation strategy of female cells) showing that Ring1B/Rnf2 targeting and H2A monoubiquitylation occur independently of H3 Lys-27 modifications (24). One such complex may be the E2F6.com-1 complex (25), which contains a subset of PcG proteins, transcription factors, and an H3 Lys-9 histone methyltransferase.…”
mentioning
confidence: 99%